Immunomodulatory responses of toll like receptors against 2019nCoV - Amany Sayed Maghraby (Russian Open Medical Journal)
The present review discusses the immune signals via toll like receptors (TLRs) against 2019nCoV. We researched using different database, up to June 18th, 2020. All the included articles were published in English language. The outcome of this review, that some TLRs agonists or antagonists are progressed as drugs to combat and down regulating TLRs immune signals respectively. TLRs 3 and 4 recognized 2019nCoV spike protein through immune and molecular signals that leading to immune stimulation of pro-inflammatory cytokines and even the immune fever. While the TLRs7 and 8 recognized single-stranded ribonucleic acids (ssRNAs) leading to elevation of the tumour necrosis factor α (TNF-α), interleukin (IL)-6 and -12 levels. TLRs agonists or antagonists utilized as immunotherapeutic targets against 2019nCoV via TLRs signals. Chloroquine and hydroxychloroquine; the approval compounds for 2019nCoV therapy can be inhibiting the class II major histocompatibility complex molecules expression and antigen presentation and even immune suppressions of the pro-inflammatory cytokines profile.